The Influence of Intrinsic Motivation And Motivation Extrinsic To Success breast milk Exclusive On Baby In Region Work Public health center Pagal - Miftakhur Rohmah; Nining Istighosah; Avelina Nelci Paju (Journal of Health Science Community, 2024)
Mother’s milk (ASI) is the best food for babies, with its nutritional content Which very special And perfect in accordance with grow flower baby, with digestion Which easy. Factor Which can support success Mother in One of the ways to provide exclusive breastfeeding to babies is support from the family can provide support to breastfeeding mothers in the form of support information instrumental, appraisal support and emotional support. Motivation is also a factor mothers to provide exclusive breast milk to their babies both internally and externally, This motivation also influences mothers not to give exclusive breast milk to their babies. Objective general Study This that is For Analyze Influence Motivation Intrinsic And Motivation Extrinsic To Success breast milk exclusive on baby in region Work Public health center Pagal. The research is quantitative with descriptive correlation research with an approach cross-sectional. The sample in this study consisted of 52 respondents. Sampling technique used in this research was simple random sampling. Data collection or the instrument used is a questionnaire. Analysis to see the influence between The dependent and independent variables use the Chi Square statistical test with levels significant α = 0.05. The research results show that there is the influence of intrinsic motivation and motivation Extrinsic to the success of exclusive breastfeeding for babies in the Pagal Community Health Center working area. From the results of the Chi square test , the value of p=0.000 (p<0.05) was obtained. So it can be concluded that There is Influence Motivation Intrinsic And Motivation Extrinsic To Success Asi exclusive on baby in region Work Pagal Health Center. Motivation is one of the factors for mothers to give exclusive breast milk to their babies, Because motivation is strength for Mother Good in a way internal nor external Which motivating somebody For reach objective specific. Motivation here it is Which Also influence Mother For give breast milk exclusive to the baby. Support person nearest like husband And family role important related problem psychic Mother breast-feed